Wrinkling deformation and thermal conductivity of one graphane sheet under shear. (1st October 2013) - Shen, Haijun
Abstract : Molecular dynamics simulations were performed to investigate the wrinkling deformation of one single‐layer graphane (GA) sheet under shear, and the shear deformation was compared with that of the macromembrane under shear. Furthermore, the thermal conductivity of the wrinkled GA sheet at 300 K was calculated. Moreover, the differences of anti‐shear capability and thermal conductance between the GA and another corresponding graphene sheet are discussed. The results show that the solutions of the macromembrane are applicable to predict the wrinkling deformation of the GA sheet under shear and that both the GA and the graphene sheet under shear have comparable anti‐buckling capability, whereas the GA sheet has much lower post‐buckling load‐carrying capacity. By increasing the shear strain, the thermal conductivity of both the GA and the graphene sheets decreases, and under the same shear strain the graphene sheet has higher thermal conductivity than the GA sheet.